Opyt grammatiki aleutsko-lisʹevskago iazyka : Sviashchennika I. Venʹiaminova, v Unalashkie. - 880-01 Innokentiĭ, Saint, Metropolitan of Moscow and Kolomna, 1797-1879. (Sanktpeterburg : V Tip. Imperatorskoĭ akademii nauk, 1846)
With Aleutian-Russian vocabularies. Mode of access: Internet.